Integrasi Smartphone Terstruktur dalam Pembelajaran Matematika: Pengaruhnya terhadap Pemahaman Matematis dan Motivasi Belajar Siswa - Hanifah (Journal of Research in Science and Mathematics Education, 2026)
Purpose: This study examines the relationship between smartphone use and two key learning outcomes in secondary mathematics education: students’ mathematical understanding and mathematics learning motivation. The increasing availability of mobile technologies has created new opportunities for integrating digital resources into classroom instruction. However, the educational impact of smartphones depends largely on how they are pedagogically implemented. This research therefore investigates whether guided smartphone use during mathematics learning is associated with improvements in students’ conceptual understanding and learning motivation. Methodology: A quantitative correlational design was employed involving 57 Grade X students from a public secondary school in Indonesia. Data were collected using a mathematical understanding test and a mathematics learning motivation questionnaire following one semester of smartphone‑supported learning. Data analysis included descriptive statistics, normality and linearity testing, and simple linear regression analysis. Findings: The results indicate that smartphone integration is positively associated with students’ mathematical understanding and learning motivation, although the magnitude of the explained variance is relatively modest. Significance: These findings suggest that smartphones can function as supportive learning tools when integrated through structured pedagogical activities that encourage conceptual exploration and collaborative discussion. The study contributes to the growing literature on mobile learning in mathematics education by highlighting the importance of teacher‑guided smartphone integration in supporting both cognitive and motivational aspects of learning.